LIBRARY AND INFORMATIO–EDUCATIONAL SPACE OF UNIVERSITY - Shytykova, Tetiana M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In this article the library is considered as a part of university information space, activity of scientific literature service department in information support of educational activity and university scientific research is presented.